Hand Load Analysis Using Text Mining Based on Letter Frequency of Indonesian Language Theses Documents - Akbar Rizki; Barokaturrizkia Ameliani; Abdul Aziz Nurussadad; Bagus Sartono; Itasia Dina Sulvianti; Auzi Asfarian (International Journal of Science, Engineering, and Information Technology, 2023)
Scientific documents contain valuable knowledge which can be discovered using text analysis. Meanwhile, the act of typing the text may discover the psychological and health condition. The hand load of the typer is essential information for designing a better keyboard, which is relevant to students' well-being in higher education institutions. This study aims to analyze the hand load of students when typing their theses in the Indonesian language. We calculate letter frequency in the Indonesian language theses documents, examine the hand load balance based on letter position on a QWERTY keyboard, identify letter hotspots, and examine hand alternation using circular visualization. The results are that the left hand has the higher load hand, indicated by the most frequent letter appearing in the documents and the letter W as the hotspot, located on the keyboard's left side. Moreover, hand alternations based on the sequence of Indonesian text identify a significant high alteration of letters from the left to the left side when typing Indonesian documents using the QWERTY keyboard. This result confirmed that the left hand has more load and less time to take a break than the right hand.